Serum Oxidative Stress-related Biomarkers in Ocular Hypertension and Glaucoma - Mine Esen Baris; Onur Furundaoturan; Meltem Kocamanoğlu; Seray Sahin; Yasemin Akçay; Suzan Güven Yılmaz (Journal of Ophthalmic & Vision Research)
Purpose: To evaluate the serum levels of oxidative stress-related molecules in patients with ocular hypertension (OHT) and primary open-angle glaucoma (POAG) compared with healthy controls. Methods: Treatment-naive patients with no known systemic diseases and with OHT and POAG diagnosis were recruited for the study. Also, age- and gender-matched healthy volunteers with no ocular and systemic diseases were included as controls. None of the participants were under any topical or systemic treatment or vitamin/antioxidant supplements. Smokers were excluded from the study. Serum levels of total antioxidant capacity (TAC), ascorbic acid, protein carbonyls (PCs), advanced glycation end products (AGEs), neuronal pentraxin 2 (NPTX2), and β-amyloid precursor protein(Aβ) were analyzed. Results: A total of 90 patients (30 in each group) were included in the study. There was no statistically significant difference between the study groups in terms of age and gender distribution. Serum levels of TAC (1.47 ± 0.11 mmole/L) were significantly higher in patients with OHT compared to controls (1.40 ± 0.11 mmole/L) and patients with POAG (1.30 ± 0.08 mmole/L) (P < 0.05). However, there was no significant difference between the study groups in terms of serum levels of ascorbic acid, PCs, AGEs, NPTX2, and Aβ. Conclusion: Serum levels of TAC were significantly higher in patients with OHT. This elevated level might contribute to the protection of the optic nerve even in the presence of increased intraocular pressure.